2017
DOI: 10.1186/s12941-017-0194-0
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic resistance and biofilm production among the strains of Staphylococcus aureus isolated from pus/wound swab samples in a tertiary care hospital in Nepal

Abstract: BackgroundThe increasing drug resistance along with inducible clindamycin resistance, methicillin resistance and biofilm production among the strains of Staphylococcus aureus are present as the serious problems to the successful treatment of the infections caused by S. aureus. So, the main objectives of this study were to determine the antimicrobial susceptibility patterns along with the rates of inducible clindamycin resistance, methicillin resistance and biofilm production among the strains of S. aureus isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
51
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 17 publications
14
51
10
Order By: Relevance
“…Resistance to erythromycin, sulfamethoxazole-trimethoprim and clindamycin reached 58%, 43% and 28%, respectively. Particularly among the MRSA, the prevalence of resistant to those antibiotics was very elevate (87%, 83% and 60%, respectively) in comparison to the rates reported in previous studies [20][21][22]. Nowadays, it is common to see such resistance profiles, especially against clindamycin, due to haphazard use of these antibiotics [22].…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Resistance to erythromycin, sulfamethoxazole-trimethoprim and clindamycin reached 58%, 43% and 28%, respectively. Particularly among the MRSA, the prevalence of resistant to those antibiotics was very elevate (87%, 83% and 60%, respectively) in comparison to the rates reported in previous studies [20][21][22]. Nowadays, it is common to see such resistance profiles, especially against clindamycin, due to haphazard use of these antibiotics [22].…”
Section: Resultsmentioning
confidence: 64%
“…Other studies have also reported high prevalence of MRSA in clinical samples [20][21][22]. Nowadays, vancomycin is used as drug of choice for treating MRSA, but the emergence of vancomycin intermediate-sensitive S. aureus (VISA) and vancomycin-resistant S. aureus (VRSA) has limited even this therapeutic route [2].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also reported high prevalence of MRSA in clinical samples [20][21][22]. Nowadays, vancomycin is used as drug of choice for treating MRSA, but the emergence of vancomycin intermediate-sensitive S. aureus (VISA) and vancomycin-resistant S. aureus (VRSA) has limited even this therapeutic route [2].…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic resistance has been one of the biggest threats for environmental, public, and veterinary health resulting in the failure of treatment, cost of treatment, and the increase in morbidity and mortality of the MS in Nepal (Thapa et al 2016;Baral et al 2013;Belbase et al 2017). This issue is evidenced by identification of the resistivity of one or more antibiotic/s to Acinetobacter, Citrobacter, Enterobacter, E. coli, Mycobacterium tuberculosis, Pseudomonas, Vibrio cholerae, Klebsiella pneumoniae, Proteus, Staphylococcus, Streptococcus pneumoniae, S. pyogenes, Shigella spp., S. typhi, S. paratyphi A, Salmonella species, Neisseria gonorrhoeae, in clinical, subclinical, veterinary, and environmental samples (Lamichhane et al 2014;Chaudhary et al 2017;Rijal et al 2017;Bansal et al 2015;Dhakal et al 2007).…”
Section: Antibiotic Resistivity and Human And Wildlife Healthmentioning
confidence: 99%